Tatyana Yakovlevna Serebryakova: a forgotten hemp expert - J. M. McPartland (Труды по прикладной ботанике, генетике и селекции)
Tatyana Yakovlevna Serebryakova (1893-?) conducted taxonomic research on Cannabis sativa L. for 20 years. She published important papers and a book on the subject. Next to every great man stands a great woman, and Serebryakova was Vavilov’s hemp expert. Yet her biography has never been written, and many details are lost. We have reconstructed her history based on historical archives, her publications, and her-barium specimen labels. Highlights of her scientific contributions are presented.